THREAT ANALYSIS OF REASONS LEADING TO FAILURE OF PERMANENT HEAMODIALYSIS ACCESS - Siyar, Falak; Jamil, Muhammad; Ali, Kishwar; Latif, Humera; Pervaiz, Hafiz Khalid; Kharl, Rai Ahmad Khan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To analyze the commonest threats which lead to the failure of a permanent vascular haemodialysis access. Study Design: Prospective observational study. Place and Duration of Study: Department of Vascular Surgery, Combined Military Hospital Rawalpindi, from Nov 2018 to Nov 2019. Methodology: All patients who presented with arteriovenous fistula (AVF) or arteriovenous graft (AVG) related complications which can potentially fail an access were included. The frequency, with which these complications occurred, was noted. Results: A total of 158 patients were included, 73 (46.20%) were male and 85 (53.80%) were females. The complications observed in order of frequency were arteriovenous fistulathrombosis (anastomotic or draining vein) in 60 (38%), pseudo aneurysms in 39 (24.68%), stealing veins causing non-maturity of the access in 14 (8.86%), venous hypertension causing extremity edema in 14 (8.86%) (7 due to stealing veins and 7 due to central venous stenosis), AVF anastomotic or draining vein stenosis in 8 (5.06%), wound hematoma in 5 (3.16%), wound infection in 5 (3.16%), true aneurysm of the draining vein in 4 (2.56%), steal syndrome in 3 (1.9%), wound seroma in 3 (1.9%), post op arm edema(not related to central vein stenosis or stealing veins) in 2 (1.26%) and compression neuropathy in 1 (0.6%) of the patients. Conclusion: Complications of vascular access are the potential threats to the life of a permanent vascular access. Early diagnosis and timely intervention can help in fistula salvage.